PENERAPAN ARTIFICIAL INTELLIGENCE, MACHINE LEARNING DAN DEEP LEARNING PADA KURIKULUM AKUNTANSI - A SYSTEMATIC LITERATURE REVIEW - Kesia Athania Purba; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
This research aims to determine the importance of implementing artificial intelligence, machine learning and deep learning in accounting curriculum in accounting education institutions based on published research articles. This research also aims to explore the gaps in science to develop future academic studies. This research uses the systematic literature review (SLR) method to analyze various articles published in academic journals indexed in Scopus published in 2020 to 2023. Articles were filtered using the specified keywords obtained from various top-ranked journals so that twenty articles were reviewed. The SLR method was used to examine the topic/theme, results, methodology, recommendations and limitations of the published articles. The results of the analysis provide evidence that accounting education institutions need to keep up with the latest developments in digital technology so that the future accountants produced have good technological skills. In line with the possible changes in accounting skills needed in the future, accountants must try to deal with the changes brought by technology. New technologies such as artificial intelligence, machine learning and deep learning should be adopted to maximize the opportunities that will be obtained in the coming years. The findings are expected to provide substantial benefits to educational institutions in adapting the accounting curriculum to digital developments to produce accounting graduates who are able to compete in the labor market.